2017
DOI: 10.1371/journal.pone.0178514
|View full text |Cite
|
Sign up to set email alerts
|

Shaofu Zhuyu decoction ameliorates obesity-mediated hepatic steatosis and systemic inflammation by regulating metabolic pathways

Abstract: Shaofu Zhuyu decoction (SFZYD, also known as Sobokchugeo-tang), a classical prescription drug in traditional East Asian medicine, has been used to treat blood stasis syndrome (BSS). Hepatic steatosis is the result of excess caloric intake, and its pathogenesis involves internal retention of phlegm and dampness, blood stasis, and liver Qi stagnation. To evaluate the effects of treatment with SFZYD on obesity-induced inflammation and hepatic steatosis, we fed male C57BL/6N mice a high fat diet (HFD) for 8 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…This included reducing the Firmicutes/Bacteroidetes ratio and increasing the abundance of Ruminococcaceae , which could restore the impaired intestinal barrier function and indirectly alleviate the inflammatory response of rats with endometriosis as we have discussed above. It is worth noting that SFZYD has been shown to reduce inflammation and promote lipid metabolism in a high-fat diet mouse model [ 38 ]. In addition, the network pharmacology analysis showed that the lipid metabolism-related pathway constituted potential protein targets of SFZYD [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This included reducing the Firmicutes/Bacteroidetes ratio and increasing the abundance of Ruminococcaceae , which could restore the impaired intestinal barrier function and indirectly alleviate the inflammatory response of rats with endometriosis as we have discussed above. It is worth noting that SFZYD has been shown to reduce inflammation and promote lipid metabolism in a high-fat diet mouse model [ 38 ]. In addition, the network pharmacology analysis showed that the lipid metabolism-related pathway constituted potential protein targets of SFZYD [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, MDG-1 treatment could up-regulate the levels of SCFAs (especially butanedioic acid) and slightly alter the contents of amino acids based on the GC-TOF/MS analysis of fecal samples [ 24 ]. Moreover, researches indicated that SCFAs [ 26 , 27 ] and some amino acids [ 28 , 29 ] have been proven to impact de novo synthesis of lipids and glucose. Taken together, the core signaling pathways which MDG-1 influenced might interact together, thus exerting beneficial effects on obesity and abnormal lipids in HF mice.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese medicine has been used for a long time for treating diseases, playing an important role in the treatment of obesity. 10,11 In this paper, we selected drugs that have been widely discussed in obesity-related metabolic studies and can be used in clinical practice without obvious toxic and side effects, such as ginsenoside (Ginseng), 12 celastrol (Tripterygium wilfordii), 13 berberine (Coptis chinensis), 14 curcumin (Turmeric), 15 and the Xiexin 16 and Danggui Buxue decoctions. 17 Considering that different organ tissues may play similar weight-reducing roles under the role of TCM or TCM extracts in the weight-reducing process, we will mainly generalize from the specific mechanisms (regulating fat metabolism, intestinal Microflora, and regulating hormone level, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine has been used for a long time for treating diseases, playing an important role in the treatment of obesity. 10 , 11…”
Section: Introductionmentioning
confidence: 99%